Gerçek zamanlı 5G teknoloji geliştirme platformu - Gemici, Ömer Faruk; Kara, Fatih; Hökelek, İbrahim; Salim, Irwan H.; Asmer, H. J.; Köksal, M. İlter; Telli, Ali; Yazar, Ahmet; Arslan, Hüseyin (IEEE, 2017)
Advancing the readiness level of 5G technologies requires hardware development activities, where the infrastructure has outmost importance. In this paper, we present multicore ARM-DSP based 5G technology development platform which will expedite commercializing the findings of the 5G researches. In the proposed platform, multicore DSP processors with enourmous signal processing capabilities are used to realize the real-time implementation of 5G physical layer algorithms while multicore ARM processors running real-time operating system are used to implement the real-time implementation of 5G higher layer protocols. To demonstrate the efficiency of the proposed platform, the proof of concept implementation of both transmitter and receiver algorithms within multicore DSP processors are performed for 20 MHz bandwidth and the real-time video transmission over the air using the USRP radios are successfully demonstrated. This platform will be made available to researchers to support 5G R&D activities.

5G teknolojilerinin olgunluk seviyelerinin yükseltilmesi donanım geliştirme faaliyetlerini gerektirir ve altyapının yeterliliği önem arz etmektedir. Bu bildiride, 5G araştırma sonuçlarının ürünleşmesine destek olmak amacıyla çok çekirdekli ARM-DSP yonga kümesi üzerinde geliştirilen 5G teknoloji geliştirme platformu sunulmaktadır. Önerilen platformda, fiziksel katman yazılımlarının gerçek zamanlı koşması için yüksek sinyal işleme yeteneğine sahip ve paralel çalışabilen çok çekirdekli DSP işlemciler kullanılırken üst katman yazılımları için üzerinde tümleşik işletim sistemlerinin çalıştırıldığı ARM işlemciler kullanılmaktadır. Önerilen mimarinin verimliliğini göstermek amacıyla 20 MHz bant genişliğinde çalışan fiziksel katman alıcı ve verici yazılımları çok çekirdekli DSP mimarisinde geliştirilmiş ve USRP radyolar ile gerçek zamanlı video transferi başarılı bir şekilde gösterilmiştir. 5G araştırma geliştirme faaliyetlerini desteklemek amacıyla bu platformun araştırmacıların hizmetine sunulması planlanmaktadır.
Real-time 5G technology development platform
Keywords: Kablosuz İletişim; 5G; Modem; Prototip; Wireless Communications; 5G; Modem; Prototyp